2019
DOI: 10.1038/s41598-019-38535-5
|View full text |Cite
|
Sign up to set email alerts
|

Redox-regulation and life-history trade-offs: scavenging mitochondrial ROS improves growth in a wild bird

Abstract: It has been proposed that animals usually restrain their growth because fast growth leads to an increased production of mitochondrial reactive oxygen species (mtROS), which can damage mitochondrial DNA and promote mitochondrial dysfunction. Here, we explicitly test whether this occurs in a wild bird by supplementing chicks with a mitochondria-targeted ROS scavenger, mitoubiquinone (mitoQ), and examining growth rates and mtDNA damage. In the yellow-legged gull Larus michahellis, mitoQ supplementation increased … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
11
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 20 publications
(12 citation statements)
references
References 72 publications
1
11
0
Order By: Relevance
“…The reason of this contradictory result is puzzling. A recent study 67 found CS activity in blood cells of chicks of yellow-legged gull ( Larus michahellis ) was negatively correlated with mtDNA damage, indicating a negative relationship between oxidative damage and mitochondrial activity. Nevertheless, biochemical variables and oxidative damage in gull chicks were also correlated with growth rate.…”
Section: Discussionmentioning
confidence: 95%
“…The reason of this contradictory result is puzzling. A recent study 67 found CS activity in blood cells of chicks of yellow-legged gull ( Larus michahellis ) was negatively correlated with mtDNA damage, indicating a negative relationship between oxidative damage and mitochondrial activity. Nevertheless, biochemical variables and oxidative damage in gull chicks were also correlated with growth rate.…”
Section: Discussionmentioning
confidence: 95%
“…Hence, it is plausible that chicks in the mismatched groups accumulated more damage as a consequence of fast growth (including mitochondrial damage; see e.g. [55]) than chicks in the matched groups but such an effect was not mirrored in MDA levels. Importantly, previous studies have shown that increased postnatal growth rate and oxidative stress levels are important factors accelerating telomere attrition (reviewed in [56,57]).…”
Section: Discussionmentioning
confidence: 99%
“…As an example, one of the first cellular lines of defence against pro‐oxidants is the reduced form of glutathione, the production of which can increase in response to stress events (Angelier et al., 2018). An increased availability of ROS scavengers can allow greater metabolic activity, as demonstrated in endotherms through enhanced growth (Velando, Noguera, da Silva, & Kim, 2019). However, there is little knowledge about the costs of increased ROS scavenger production—note that ROS are known to play an essential role in signalling pathways (Costantini, 2019).…”
Section: Candidate Mechanisms To Buffer the Effects Of Warming On Agementioning
confidence: 99%